The Power of Instagram's Algorithm in Boosting the Visibility of Startups & Small Businesses - Dr. Sana Saima; Dr. Sachin Parappagoudar; Ananya Hariharan; Vishesh S Setty`; Aditya Ashok Jain; Aanchal Jain; Aditya P Jain; Aman R Jain; Darshan Banka (International Journal of Engineering and Management Research, 2023)
As the world progresses towards digitalized platforms for ease of access, social media is getting more popular amidst the younger generations, causing marketers to quickly adapt to the social networking space to be able to interact with customers. India is one of the world’s fastest growing economies, with startups contributing approximately 4-5% to the nation’s gdp. The metropolitan city of bangalore serves as a hub for many up-and-coming startups and small businesses. Networking is crucial for small businesses, as word-of-mouth referrals can boost sales. Social media marketing is a cost-effective way to reach a broader audience and engage with customers. Additionally, traditional advertising channels such as billboards, flyers, and newspaper ads can still be effective in certain regions. In order to stand out in a saturated market such as ours, it is essential to strategize and create a marketing campaign that taps into the resources offered by interactive social media platforms the likes of instagram, facebook and many others. Through social media, big business can do better and small business can become better known without putting much investment on advertising. This study aims to provide insight into the seemingly vast marketing tool often underestimated by many – instagram’s algorithm.